ANALYSIS & OPTIMIZATION STUDY OF BATTERY CHARGER FOR MOBILE APPLICATION - ZAIDEEN, NUR HAZIRA (IRC, 2019)
A battery charger is a mechanism that places energy into a secondary cell or rechargeable battery by allowing electric current through it. In this work, the optimization of battery charging method for mobile phone will be carried out. This is due to the different kind of charging method and the battery charger. The type of charger in this work is focusing on recharging lithium-ion battery type. A good charger enables battery charging capability with appropriate time without damaging the battery. Thus, the right way of charging a phone needs to be done. It is found that the ideal/normal charging method is the best method to charge a mobile found. This is due to the balance amount of current and voltage supplied to the battery according to time. The discharging process of the battery also is longer than other methods of charging.